LEGAL ANALYSIS OF CHILDREN SEXUAL VIOLENCE CRIMINAL ACTS (STUDI KASUS PERKARA NOMOR: 86/PID.SUS/2022/PT BDG) - Marcika Rizky Hidayah Putri; Zainal Arifin Hoesein; Moh Zakky (Jurnal Hukum Jurisdictie, 2023)
Children are God's creations that need to be protected by anyone because of their limitations. One of the protections provided is legal protection for children who get a form of violence. Violence that children receive will have a negative impact on the child's future. This paper aims to find out the need to provide legal protection for children as victims of violence and legal protection for children as victims of violence according to statutory regulations. To find out this, normative research was carried out by studying and researching laws and regulations related to child protection. The need for normative legal research in order to know the legal protection for children as victims of violence. The problems formulated in this research are, firstly, why children who are victims of violence need to be given legal protection, and secondly, how is legal protection for children who are victims of violence according to statutory regulations. Legal protection for children is given so that children's rights are protected as stated in the laws and regulations governing child protection, namely not getting forms of violence as stated in Articles 76A to 76B Law Number 35 of 2014 and legal protection given for the justice of the child. Therefore, the state provides legal protection for all children which has been regulated to be implemented in Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims and Law Number 35 of 2014 concerning child protection, in order to prevent the occurrence of violence against children.